Dari Hitam ke Albino: Humor Digital sebagai Dekonstruksi Stigma Mistis pada Hewan - Putri Dian Afrinda; Iswadi Bahardur; Muhamad Fuad Bin Abdul Karim (Lingua Susastra, 2026)
This study examines the YouTube short video titled “KEMARAHAN PARA HEWAN KE MANUSIA!!!” as a case study of digital humor critiquing mystical stigma against animals. The video features personifications of a black cat, black crow, black chicken, and albino crocodile protesting human labeling. This research aims to reveal the construction of cultural signs, humor mechanisms, and linguistic strategies in delivering critique. A qualitative descriptive-interpretative approach is employed with an integrated analytical framework: Roland Barthes' semiotics, humor theory (Incongruity and Script Opposition), and digital sociolinguistics. The findings show that the albino crocodile serves as a pivot, expanding the critique from black-color-based stigma to the mystification mechanism against bodies perceived as “other,” rare, or atypical. Humor is constructed through role reversal and script opposition between mystical and critical perspectives, while informal language (gue, guys, boleh join?) functions as a pragmatic mitigation strategy that softens critique without being patronizing. The study concludes that digital humor in this video functions as myth deconstruction and critique of the cultural tendency to marginalize physical differences.